Long‐term stability (21–30 years) of root coverage outcomes using sub‐epithelial connective tissue grafts at single or multiple gingival recessions: A longitudinal case series - Bertoldi, Carlo; Consolo, Ugo; Lalla, Michele; Zaffe, Davide; Tanza, Donato; Cairo, Francesco; Cortellini, Pierpaolo (Journal of clinical periodontology, 2024)
Aim To evaluate outcomes and predictive factors for the long‐term stability of root coverage using a sub‐epithelial connective tissue graft. Materials and Methods One‐hundred and two healthy subjects (221 gingival recessions, GRs) were treated from 1987 to 1996. Keratinized tissue width (KTW), GR depth (RD), GR width (RW) and GR area (RA) were evaluated at baseline (M0) and at 1 month (M1), 1 year (M2), 11 years (M3), 21 years (M4) and 27 years (M5) after surgery. Primary outcomes consisted of complete root coverage (cRC) and relative dimensional changes in recession depth (measured in mm [c%‐RD]), recession width (measured in mm [c%‐RW]) and recession area (measured in mm2 [c%‐RA]). Results cRC was 88.7% at 1 year (M2), 59.8% at M3, 44.4% at M4 and 51.9% at M5. Average c%‐RD was 95.2% at 1 year, 81.9% at M3, 71.5% at M4 and 81.7% at M5. KTW increased after surgery and over time and was positively correlated with favourable outcomes. Increased baseline RA was associated with less favourable clinical outcomes. Conclusions The sub‐epithelial connective tissue graft is effective in the treatment of GRs and facilitates long‐term stability of clinical outcomes. Wider baseline RA was a strong predictor of unfavourable short‐ and long‐term RC outcomes.